PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR IPA METERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI PADA SISWA KELAS IV SD NEGERI 93 AMBON: Indonesia - Fitrin; Rumahlatu, Dominggus; Pelamonia, Johanes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using the project-based learning model on science learning outcomes for the material on plants as sources of life on earth for fourth-grade students at SD Negeri 93 Ambon. The method used was experimental research using a quasi-experimental design. The results showed that the use of the project-based learning model had an effect on students' science learning outcomes for the material on plants as sources of life on earth.